Epidemiology and treatment outcomes of testicular germ cell tumor at tertiary care center in Patna, India: A retrospective analysis - Singh, Dharmendra; Singh, Pritanjali; Mandal, Avik (Asian Pacific Journal of Cancer Care, 2020)
Background: Malignant testicular neoplasm constitutes about 1% of all cancers in male, but malignant germ cell tumors are most common tumors in adolescents and young adult males. In this study we report our experience of testicular germ cell tumors presenting at All India Institute of Medical Sciences, Patna, a tertiary referral centre, with respect to epidemiology, histopathology, management and outcome. Methods: This study was conducted in department of Radiotherapy, All India Institute of Medical Sciences, Patna from August 2014 to September 2019. It was single institution based retrospective study in which data was retrieved from the recorded files & analysed. The study focused on epidemiology and survival outcomes. Results: In this study we analysed, 38 histologically confirmed cases of testicular germ cell tumor. Seminoma and nonseminoma were 50% (19) and 50% (19) respectively. The median age was 31 years. The most common affected age group was 31 to 40 years. Metastasis was present in 50% of patients at presentation. At diagnosis the stage III, II and I were found in 50%, 28.9% and 21.1% respectively. Patients in good risk, intermediate risk and high risk were in 65.8%, 13.2% and 21.1% respectively. The median recurrence free survival (RFS) and overall survival (OS) was 52 months and 71 months respectively. Conclusion: Most of the cases presented with advanced stage and majority of them had undergone high inguinal orchidectomy. The high nodal burden disease at presentation was associated with partial response to standard chemotherapy. It seems that there is the need of alternative chemotherapy regimen especially in nonseminomatous germ cell tumors. Patients presenting with disease confined to locoregional lymph nodes or local disease showed good prognosis.